Having the conversation about work with people with multiple sclerosis: a guide for healthcare professionals. (November 2017) - Cardone, Antonella
The ability to work is important for people with multiple sclerosis (MS). However, only 37% of those with mild MS are in work. Across Europe, lost work productivity accounts for a third of the €15 billion total annual cost of MS. Supporting people with MS into employment should be a clinical care priority in order to maximize work productivity, inclusiveness and therapeutic benefit. A guide for healthcare professionals on having conversations about work with people with MS has been developed through the 'Ready for Work' project. Work should be considered as a clinical outcome. The focus should be on what patients can do, rather than what they cannot do, at work. Effective communication is fundamental in supporting patients' return to work.